Work-Family Conflict and Family-Work Conflict as Mediating Variables in Workload and Social Support for Work Stress (The Case of Female Workers in Creative Indus-tries) - Novita Lis Setiyawan; Santi Rimadias (Indonesia Banking School, 2021)
This study aims to analyze how workload and social support affect work stress with work-family conflict and family-work conflict as mediation variables. The samples used in the study were 225 female employ-ees working in the creative industries. Female employees in the creative sectors were given surveys in the form of Google forms as part of the study's data collection methodology. The data analysis method used in this research is Structural Equation Modelling (SEM) analysis and processed using AMOS 23 applications. The results of analysis using SEM showed that Work-family conflict mediates the relationship between workload and job stress. Family-work conflict mediates the relationship between workload and job stress. Work-family conflict does not mediate the relationship between supervisor support and job stress. Family-work conflict mediates the relationship between supervisor support and job stress. Work-family conflict mediates the relationship between family support and job stress. Family-work conflict mediates the rela-tionship between family support and job stress. Work-family support mediates the relationship between organizational support for reconciling and job stress and Family-work conflict mediates the relationship between organizational support for reconciling and job stress. The importance of more support provided by families and organizations for the management of work stress of female workers in the creative industry.